Bridgeless Isolated Cuk PFC Implementation using PID and Neural Controller - R. Pireethi; R. Balamurugan (Institute of Advanced Engineering and Science, 2016)
The comparision of Bridgeless Isolated Cuk converter using Proportional Integral Derivative (PID) and Neural controller (NC) is presented in this paper. Due to Diode Bridge Rectifier (DBR) conventional converters suffer from high conduction loss. Bridgeless Cuk converter is used to eliminate the issues. Bridgeless Isolated (BLI) Cuk converter is used to withstand high voltage. Compare to Continuous Conduction Mode (CCM) Discontinuous Conduction Mode (DCM) utilize less number of sensors. To obtain unity power factor it is used to work in DCM mode. BLI Cuk Converter is implemented in two controller PID and Neural controller to observe power factor. Performance of BLDC motor is simulated by using MATLAB/SIMULINK software.